Bundle methods for nonsmooth DC optimization - Kaisa Joki; Adil M. Bagirov (Springer, 2025)
This chapter is devoted to algorithms for solving nonsmooth unconstrained difference of convex optimization problems. Different types of stationarity conditions are discussed and the relationship between sets of different stationary points (critical, Clarke stationary and inf-stationary) is established. Bundle methods are developed based on a nonconvex piecewise linear model of the objective function and the convergence of these methods is studied. Numerical results are presented to demonstrate the performance of the methods.
Numerical Nonsmooth Optimization: State of the Art Algorithms